Impact of Latent Virus Infection in the Cornea on Corneal Healing after Small Incision Lenticule Extraction - Ming Liu; Wenting Song; Wen Gao; Lili Jiang; Hongbiao Pan; Dan Luo; Lei Shi (Microorganisms, 2023)
The aim of the present study is to analyze the impact of cornea virus latent infection on corneal healing after small incision lenticule extraction (SMILE) and predict the positive rate of virus latent infection in corneal stroma. A total of 279 patients who underwent SMILE were included in this study. Fluorescence quantitative PCR was used to detect virus infection in the lenticules, which were taken from the corneal stroma during SMILE. Herpes simplex virus type 1 (HSV-1), herpes simplex virus type 2 (HSV-2), Epstein–Barr virus (EBV), and cytomegalovirus (CMV) were detected. Postoperative visual acuity, spherical equivalent, intraocular pressure, corneal curvature (Kf and Ks), corneal transparency, and corneal staining were compared between the virus-positive group and the virus-negative group. The number of corneal stromal cells and inflammatory cells, corneal nerve fiber density (CNFD), corneal nerve branch density (CNBD), corneal nerve fiber length (CNFL), corneal total branch density (CTBD), and corneal nerve fiber width (CNFW) were evaluated using an in vivo confocal microscope. Out of 240 herpes simplex virus (HSV) tested samples, 11 (4.58%) were positive, among which 5 (2.08%) were HSV-1-positive and 6 (2.50%) were HSV-2-positive. None of the 91 CMV- and EBV-tested samples were positive. There was no statistical significance in the postoperative visual acuity, spherical equivalent, intraocular pressure, Kf and Ks, corneal transparency, corneal staining, the number of corneal stromal cells and inflammatory cells, CNFD, CNBD, CNFL, CTBD, and CNFW between the virus-positive and virus-negative groups (p > 0.05). In conclusion, there is a certain proportion of latent HSV infection in the myopia population. Femtosecond lasers are less likely to activate a latent infection of HSV in the cornea. The latent infection of HSV has no significant impact on corneal healing after SMILE.